Community participation patterns among preschool‐aged children who have received Part C early intervention services. Issue 4 (13th June 2013) - Khetani, M.; Graham, J. E.; Alvord, C.
Abstract Background We examined activity‐specific patterns and child, family and environmental correlates of participation restriction in nine community‐based activities among preschoolers with disabilities who have received Part C early intervention services. Methods Data were gathered from a subsample of 1509 caregivers whose children (mean age = 67.7 months) had enrolled in the National Early Intervention Longitudinal Study (NEILS) and completed a 40‐min computerized telephone interview or 12‐page mailed survey. Data were analysed on cases with complete data on the variables of interest. Bivariate relationships were examined between variables, including patterns of co‐reporting participation difficulties for pairs of community activities. Results Caregivers were more than twice as likely to report difficulty in one activity (20%) than difficulties in 2–3, 4–5, or 6–9 activities. Co‐reporting paired difficulties was strong for activities pertaining to neighbourhood outings but less conclusive for community‐sponsored activities and recreation and leisure activities. Our data show strong and positive associations between child functional limitations in mobility, toileting, feeding, speech, safety awareness, and friendships and participation difficulty in 7–9 activities. Lower household income was associated with participation difficulty in 7 out of 9 activities and difficulty managing problematic behaviour was strongly associated with participation difficulty in all 9 activities. Each of the three environmental variables (limited access to social support, transportation and respite) was associated with participation restrictions in all nine activities. Conclusion Results provide practitioners with detailed descriptive knowledge about modifiable factors related to the child, family and environment for promoting young children's community participation, as well information to support development of a comprehensive assessment tool for research and intervention planning to promote community participation for children enrolled in early intervention.